Using Simulated Patients to Understand Non-Prescription Antibiotic Dispensing in Indonesia: A Systematic Review - Fathul Muin; Anna Wahyuni Widayanti (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2023)
Background: Dispensing antibiotics without a prescription at community pharmacies is a significant contributor to the ongoing global public health issue of antibiotic resistance. Objectives: To estimate the proportion of antibiotics that are dispensed without a prescription in community pharmacies in various Indonesian cities. Methods: A literature review was conducted via PubMed, Science Direct, Google Scholar, Garuda, and Neliti for articles published between January 2007 and December 2022 combined with Boolean operators. The literature search keywords were (simulated patientsOR mystery shopper OR sample patients OR dummy patients) AND ("antibiotics without prescription OR non-prescription antibiotics OR self-medication of antibiotics). The keywords are also used in Indonesian language (Bahasa), including "simulasi pasien” OR "sampel pasien” AND "antibiotik tanpa resep” OR "swamedikasi antibiotik”. Results: Seven studies from various cities have complied with the inclusion criteria and were considered when reviewing 199 articles. The findings of our studies were consistent with the extensive use of non-prescription antibiotics throughout the review. A simulation patient study design was used in all seven studies in this review. Amoxicillin recorded the highest percentage of dispensing without a prescription, while other drugs often purchased include chloramphenicol, ciprofloxacin, and cefadroxil. Among the studies reviewed, one study utilized the pre-test and post-test methods, while the others did not. Conclusion: The lack of prescriptions for antibiotics dispensing has often occurred in community pharmacies throughout Indonesia. The community pharmacist's role is needed as the final gate of pharmaceutical services in providing rational treatment and controlling the dispense of antibiotics without a prescription.